2015
DOI: 10.1002/adma.201500649
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap Widening of Phase Quilted, 2D MoS2 by Oxidative Intercalation

Abstract: Controllable bandgap widening from 1.8 to 2.6 eV is reported from oxidized MoS2 sheets that are composed of quilted phases of various MoSxOy flakes. The exfoliated flakes have large size (≥100 μm × 100 μm) sheets with average thickness of 1.7 nm. Remarkably, fine reversible tuning of the bandgap is achieved by postprocessing sulfurization of the MoSxOy sheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 50 publications
(64 reference statements)
8
59
0
Order By: Relevance
“…The formation of MoS 2-x O x solid solution phase has already been proposed for sputter deposited MoS 2 films 37,38 ,39 . However, so far the structure of the synthesized molybdenum oxy-sulfide films was found to be amorphous or highly disordered with poor long-range crystalline order 40,41 . Here we provide clear evidence for the formation of a highly crystalline 2D molybdenum oxy-sulfide phase and thus a strategy for synthesizing new materials through chemical transformation of 2D crystals that are difficult to synthesize by other methods.…”
Section: Ambient Oxidation Of the Basal Plane Revealed At Single-atommentioning
confidence: 99%
“…The formation of MoS 2-x O x solid solution phase has already been proposed for sputter deposited MoS 2 films 37,38 ,39 . However, so far the structure of the synthesized molybdenum oxy-sulfide films was found to be amorphous or highly disordered with poor long-range crystalline order 40,41 . Here we provide clear evidence for the formation of a highly crystalline 2D molybdenum oxy-sulfide phase and thus a strategy for synthesizing new materials through chemical transformation of 2D crystals that are difficult to synthesize by other methods.…”
Section: Ambient Oxidation Of the Basal Plane Revealed At Single-atommentioning
confidence: 99%
“…An important caveat in this analysis is that some band energies used here are those of bulk crystals, while band structures of actual 2D materials will be affected by other factors such as doping, exfoliation (thickness dependence), and compressive strain. 326330 …”
Section: Fundamental Modes Of Biological Interactionmentioning
confidence: 99%
“…27, 110, 112, 124, 215, 326, 339 Here we focus on chemical transformations with the goal of identifying the material forms that will play the most important roles in the natural environment. This issue is informed by a decade of research on the environmental implications of particulate and 1D nanomaterials 340, 341 plus significant data on the environmental chemistry of natural 2D materials.…”
Section: Chemical Transformations In the Natural Environmentmentioning
confidence: 99%
“…The material has the sheet structure with an average lateral size of about 300 nm as determined by dynamic light scattering (DLS) method (Figure B). The corresponding high‐resolution transmission electron microscopy (HR‐TEM) image (Figure C) confirmed that both MoS 2 and Bi 2 S 3 crystal lattices existed in the nanosheets, where 0.34 nm and 0.27 nm belong to the (130) plane of Bi 2 S 3 and the (101) plane of MoS 2 , respectively . Elemental distribution mappings further illustrate the co‐existence of Mo and Bi elements (Figure D).…”
Section: Figurementioning
confidence: 65%